Environmental Footprints and Occupational Hazards of Clay Mining – A Case Study from Patel Nagar, Birbhum, West Bengal, India - Saha, Bikas (The Nucleus, 2023)
Mining is one of the main economic activities of any developing country. Pressure among mining and conservation is anticipated to escalate with the growing human population and technological advancement. However, mining has both negative and positive impacts on the environment as well as on society. During mine establishment and exploitation, habitat destruction is a part of all mining activities. Clay mining has major effects on the health of local people and causes the environment to break down. Both economically and ecologically, the china clay mines of Patel Nagar in Birbhum district hold a governing position. Both geomorphological processes and environments are affected due to china clay mining. Patel Nagar and the places around have a lot of good farmlands, which suffer the adverse effects of clay mining. Hydrological cycles are getting polluted along with the degradation of landforms, soot in the air, water and noise contamination, soil corrosion, and effects on natural drainage systems in the studied area. The majority of the local poor tribal people who work in mines also have certain health-related issues as an integral part of their occupational hazards.